2023
DOI: 10.1096/fj.202200849r
|View full text |Cite
|
Sign up to set email alerts
|

CircAGK regulates high dihydrotestosterone‐induced apoptosis in DPCs through the miR‐3180‐5p/BAX axis

Abstract: The incidence of androgen alopecia (AGA), also known as seborrheic alopecia, has surged in recent years, and onset is occurring at younger ages. Dermal papilla cells (DPCs) are key to maintaining hair cycling, and apoptosis‐driven processes in DPCs are closely related to hair follicle regeneration. Circular RNAs (circRNAs) are widely present in the human body and are closely related to the occurrence and development of many diseases. Currently, the biological functions of circRNAs in AGA are largely unknown. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Wei et al found that circ_0002980 promotes dermal papilla cell apoptosis through the miR-3180-5p/BAX signaling axis. This axis mediates androgenic alopecia (AGA), providing novel targets and ideas for AGA [ 35 ]. In this study, miR-1303 was identified as a possible target miRNA of circ_0002980 using bioinformatics prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al found that circ_0002980 promotes dermal papilla cell apoptosis through the miR-3180-5p/BAX signaling axis. This axis mediates androgenic alopecia (AGA), providing novel targets and ideas for AGA [ 35 ]. In this study, miR-1303 was identified as a possible target miRNA of circ_0002980 using bioinformatics prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the precise contributions of circRNAs to AGA remain largely unexplored. Through an extensive examination of circRNA expression patterns that exploited whole-transcriptome sequencing, we identified circAGK as a promising target for focused therapeutic strategies in AGA [30] (see Fig. 2 ).…”
Section: Application Of Omics Technologies To the Study Of Agamentioning
confidence: 99%